Propuesta de plan de gestión de costos y tiempo del proyecto rehabilitación vial Samborondón - Salitre aplicando Lean Construction - Gaon Espinoza, Jhonny Ismael (2024)
Road construction and maintenance are vital for development in Ecuador and globally, but they face challenges in planning, resulting in detrimental delays. These delays incur additional costs and economic losses. The Inter-American Development Bank reports that this issue affects around 40% of road projects in Latin America and the Caribbean. In Ecuador, Ministry of Transportation statistics reveal an increase in delays over the past five years, primarily attributed to planning errors. In response, investigating the applicability of Lean Construction methodology in road project planning is proposed. This methodology is based on management principles that aim for continuous improvement and the maximization of value for the customer. The thesis focuses on the Samborondón - Salitre road rehabilitation project, aiming to enhance project efficiency and generate knowledge applicable nationally. This endeavor seeks to drive sustainable economic and social development through optimal road infrastructure.